Beneficial effect of high energy intake at lunch rather than dinner on weight loss in healthy obese women in a weight-loss program: a randomized clinical trial - Madjd, Ameneh; Taylor, Moira A.; Delavari, Alireza; Malekzadeh, Reza; MacDonald, Ian A.; Farshchi, Hamid R. (American Society for Nutrition, 2016)
ABSTRACT Background: The association between the time of nutrient intake and health has been described in a few studies. To our knowledge, no study has evaluated the relation between high energy intakes at lunch compared with at dinner on weight loss in overweight and obese subjects. Objective: We compared the effect of high energy intake at lunch with that at dinner on weight loss and cardiometabolic risk factors in women during a weight-loss program. Design: Overweight and obese women [n = 80; body mass index (BMI; in kg/m2): 27–35; age: 18–45 y] were asked to eat either a main meal at lunch (LM) or a main meal at dinner (DM) for 12 wk while in a weight-loss program. Results: A total of 80 participants were randomly assigned to one of 2 intervention groups. Sixty-nine subjects (86%) completed the trial (34 subjects in the DM group, and 35 subjects in the LM group). Baseline variables were not significantly different between groups. A significant reduction in anthropometric measurements and significant improvements in cardiometabolic risk characteristics were observed over 12 wk in both groups. Compared with the DM group, the LM group had greater mean 6 SD reductions in weight (LM: 25.85 6 1.96 kg; DM: 24.35 6 1.98 kg; P = 0.003), BMI (LM: 2.276 0.76; DM: 1.68 6 0.76; P = 0.003), homeostasis model assessment of insulin resistance (LM: 20.66 6 0.33; DM: 20.46 6 0.24; P = 0.001), and fasting insulin (LM: 22.01 6 1.10 mIU/mL; DM: 21.16 6 0.72 mIU/mL; P , 0.001) after 12 wk. However, there were no significant differences for fasting plasma glucose and lipid profiles within both groups after 12 wk. Conclusions: The consumption of higher energy intake at lunch compared with at dinner may result in favorable changes in weight loss in overweight and obese women after a weight-loss program of 12 wk. The consumption may also offer clinical benefits to improve insulin resistance. This trial was registered at clinicaltrials.gov as NCT02399280. Am J Clin Nutr doi: 10.3945/ajcn.116.134163.